Growth, Specialization, and Trade Liberalization - Michael Devereux (Queen's University, Department of Economics, 1990)
This paper examines a two-way interaction between trade liberalization and economic growth. Through dynamic increasing returns to specialization, international trade can increase world growth rates. But growth, through specialization , alters patterns of comparative advantage, changing the incentives to levy tariffs in a dynamic tariff game between governments. Two types of equilibria are analyzed. In one, average growth rates are low, tariffs are high and rising, the ratio of exports to income (the trade ratio) is low, and falls to zero asymptotically. In the other, growth rates are high, tariffs are low and falling, the trade ratio is higher, and rises over time. The conditions under which each type of equilibrium will be observed are investigated.
Keywords: 330